Fractionated Stereotactic Radiosurgery for Large Brain Metastases. (April 2015) - Wegner, Rodney E.; Leeman, Jonathan E.; Kabolizadeh, Peyman; Rwigema, Jean-Claude; Mintz, Arlan H.; Burton, Steven A.; Heron, Dwight E.
Abstract : Objectives: Large brain metastases (>3 cm) present a therapeutic dilemma, as the dose delivered by stereotactic radiosurgery (SRS) in a single fraction is limited by toxicity to adjacent tissues, resulting in suboptimal local control. This study assessed the efficacy and safety of fractionated SRS for the treatment of large brain metastases. Materials and Methods: We identified 36 patients with 37 brain metastases treated with fractionated SRS. The median SRS dose was 24 Gy (range, 12 to 27 Gy) in 2 to 5 fractions and the median treatment volume was 15.6 mL (range, 10 to 82.7 mL). Kaplan-Meier analysis was used to estimate local control and overall survival rates. Results: Of the 21 lesions with available radiographic follow-up, 6 lesions (29%) had a documented local failure, yielding an actuarial progression-free survival at 6 and 12 months of 73% and 63%, respectively. The actuarial 6-month and 1-year overall survival rates were 22% and 13%, respectively. No patients in this cohort experienced acute or late complications secondary to SRS. Conclusions: Fractionated SRS is feasible and safe in patients with large brain metastases. Local control rates appear to be improved when compared with that of single fraction SRS with a relative paucity of treatment-related toxicity.